2021
DOI: 10.1017/s0950268821001096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective removal of badgers (Meles meles) on ranging behaviour during a ‘Test and Vaccinate or Remove’ intervention in Northern Ireland

Abstract: The role of the Eurasian badger (Meles meles) as a wildlife host has complicated the management of bovine tuberculosis (bTB) in cattle. Badger ranging behaviour has previously been found to be altered by culling of badgers and has been suggested to increase the transmission of bTB either among badgers or between badgers and cattle. In 2014, a five-year bTB intervention research project in a 100 km 2 area in Northern Ireland was initiated involving selective removal of dual path platform (DPP) VetTB (immunoassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 34 publications
4
31
1
Order By: Relevance
“…During year 1, all captured badger were tested, vaccinated and released to enable the estimation of a baseline of normal ranging behaviour. 28 The field activities (land survey, cage deployment and baiting) were undertaken by 18 staff working in six three-person teams supported by a team of up to five veterinary surgeons who undertook the anaesthesia and sampling of the captured badgers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During year 1, all captured badger were tested, vaccinated and released to enable the estimation of a baseline of normal ranging behaviour. 28 The field activities (land survey, cage deployment and baiting) were undertaken by 18 staff working in six three-person teams supported by a team of up to five veterinary surgeons who undertook the anaesthesia and sampling of the captured badgers.…”
Section: Methodsmentioning
confidence: 99%
“…Swabs were also taken from any bite wounds observed on the animal. During years 1–4, a subset of badgers ( n = 40) had global positioning system collars fitted to monitor their ranging behaviour 28 . To facilitate recovery from anaesthesia, badgers were positioned in a nearby sheltered location or returned to the cage until they had recovered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we acknowledge that more spatially accurate techniques for estimating home range are available, e.g. [53,80]. Because MCP can include areas not regularly used by an animal, this method will overestimate HR size.…”
Section: Plos Onementioning
confidence: 99%
“…Importantly, data on the effects of disturbances, such as clearfelling and road building, need to be established, as well as how this relates to interspecific transmission. Gaughran et al [ 52 ] and O’Hagan et al [ 54 ] both used GPS trackers on badgers to assess the impact of road realignment and low-level culling on ranging behaviour, respectively. Both studies showed that such processes can have subtle effects on badger behaviour, which may not meaningfully contribute to increasing disease spread dynamics.…”
Section: Discussionmentioning
confidence: 99%